Molecular Structure and Vibrational Spectra of 5,7-Dichloro-8-hydroxyquinaldine by Density Functional Theory and ab initio Hartree-Fock Calculations - Arici, K.; Koksal, H. (Asian Journal of Chemistry, 2010)
The fourier transform infrared spectra and fourier transform Raman spectra of 5,7-dichloro-8- hydroxyquinaldine (5,7-DCIHQM) are recorded in solid phase. The molecular geometry, vibrational frequencies, infrared and Raman intensities of 5,7-DCIHQM in ground state have been calculated by using ab initio Hartree-Fock (HF) and density functional theory DFT(B3LYP and B3PW91) methods with 6-31G (d) basis set level. On the basis of the comparison between calculated and experimental results and the comparison with related molecule, assignments of fundamental vibrational modes are examined. The optimized geometric parameters (bond lengths and bond angles) obtained by using HF show the best agreement with the experimental values of 5,7-DCIHQM. Comparison of observed fundamental vibrational frequencies of 5,7-DCIHQM and calculated results by DFT (B3LYP and B3PW91) and HF approach for molecular vibrational problems.